Evaluation of Hearing Status in Pre and Postoperative Canal Wall Down Mastoidectomy with Type III Tympanoplasty with or without Cartilage Augmentation (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To evaluate Hearing Status in Pre and Post-operative Canal Wall Down Mastoidectomy with Type III Tympanoplasty with or without cartilage augmentation.Methods: This was a prospective study, done in Otolaryngology & Head Neck Surgery department of Sir Salimullah Medical College Mitford Hospital(SSMCMH) and Bangabandhu Sheikh Mujib Medical University(BSMMU) , Dhaka, Bangladesh. 1stJuly to 31st December, 2012. Forty patients were studied in this series.Results: The results concluded that mean pre and post-operative air bone gap were 38.5 dB and 29.69 dB respectively with a net gain of 8.81 dB in Canal wall down mastoidectomy with cartilage augmented Tympanoplasty type III which is statistically significant. The postoperative PTA-ABG ranged from 25-36 dB , the ABG closure was 11-15 dB in 40% case. Whereas mean pre and post-operative air bone gap were 37.19 dB and 34.19 dB respectively with a net gain of 3 dB in Canal wall down mastoidectomy without cartilage augmented Tympanoplasty type III which is statistically insignificant. The post-operative PTA-ABG ranged from 26.25-41.75 dB, the ABG closure was 0-5 dB in 35% case.Conclusion: Hearing results after cartilage augmentation in type iii Tympanoplasty showed improvement at individual and mean post-operative PTA-ABG and also improvement in ABG closure suggesting thin cartilage disc increased the effective vibrating area of tympanic membrane graft.Bangladesh J Otorhinolaryngol; October 2020; 26(2): 86-94